1994
DOI: 10.1055/s-2006-959493
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities ofCrataegus monogynaExtracts

Abstract: Interesting antioxidant activities of extracts from different vegetative and reproductive organs of Crataegus monogyna harvested at different stages of growth have been determined by the malondialdehyde-thiobarbituric acid (MDA) test on hepatic microsomal preparations and compared to the contents in total phenolics, proanthocyanidins, catechins, flavonoids, and phenolic acids. The best correlations were established with total phenols while activities in leaves seem to be influenced by flavonoids and in flowers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 9 publications
10
77
1
Order By: Relevance
“…Unlike the three fruit extracts (HE, HP, and HJ), the main polyphenolic components of HF were two C-glycosylflavones, of which vitexin-2 00 -rhamnoside was the more abundant (20.5%, w/w). This flavonoid profile was similar to those seen for European hawthorn leaves, 31) but this extract lacked procyanidins and other phenolics.…”
Section: Contents Of Organic Acid and Polyphenolssupporting
confidence: 75%
See 1 more Smart Citation
“…Unlike the three fruit extracts (HE, HP, and HJ), the main polyphenolic components of HF were two C-glycosylflavones, of which vitexin-2 00 -rhamnoside was the more abundant (20.5%, w/w). This flavonoid profile was similar to those seen for European hawthorn leaves, 31) but this extract lacked procyanidins and other phenolics.…”
Section: Contents Of Organic Acid and Polyphenolssupporting
confidence: 75%
“…32) Many of the chemoprotective effects of phenolics, such as procyanidins, are related to the scavenging actions of oxygen radicals, and include resistance to lipid peroxidation, 31,33) antioxidation of low density lipoproteins, 4,5,34) and protection against damage from UV or -ray irradiation. 35,36) Our results regarding the scavenging capacities of hawthorn extracts and related compounds for O 2 À and OH radicals are shown in Table 2.…”
Section: Antioxidant Activities Of Hawthorn Extracts and Related Compmentioning
confidence: 99%
“…They found that the scavenging activities of the cell suspension extracts were similar to those of the flowers. Furthermore, some reports studied the antioxidant actions of Crataegus monogyna callus cultures and showed that a high TEAC values were observed when the culture medium contained 2.0 mg/L 2,4-D and 0.5 mg/L KIN, these values were strongly influenced by the total flavonoids content (Bahorun et al 1994(Bahorun et al , 2003. In addition, Bahri-Sahloul et al showed a high DPPH radical scavenging effect in Salvia officinalis shoot cultures grown on MS medium containing a high ratio of BAP over IAA which was comparable to that of collected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Crataegus may have cardio protective properties (Chatterjee et al, 1997). Antioxidant activity of hawthorn species has already been reported (Bahorun et al, 1994, Ljubuncic et al, 2005. Hawthorn contains different phenolic and flavonoids compounds, including: chlorogenic acid, epicatechin, rutin, hyperoside and vitexin (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%